How to draw cartoons - Satyamurty.B.V (Delhi Pustak mahal, 1992)
Provides simple instructions about cartooning including the materials, shapes, funny faces, and action figures.
Includes bibliographical references (p. 24) and index.
Keywords: Cartooning; Cartooning; Drawing